Digital computerised cognitive training for preventing cognitive decline among hypertensive patients: a study protocol for a multicentre randomised controlled trial (DELIGHT trial) - Ji Guang Wang; Xin Du; Liu He; Chao Jiang; Yong Zeng; Yu Kong; Qian Hui Guo; Le Zhou; Jian Zeng Dong; Chang Sheng Ma (BMJ Open, 2024)
Introduction Mild cognitive impairment (MCI) is an important intervenable stage for the prevention of dementia. Hypertension is associated with impaired cognition, and when combined with MCI, it may lead to a poor prognosis. Digital computerised cognitive training (CCT) has recently become a potential instrument for improving cognition, but evidence for its efficacy remains limited. This study aims to evaluate the efficacy of a digital adaptive CCT intervention in older patients with hypertension and MCI.Methods and analysis The multicentre, double-blinded, randomised, actively -controlled clinical trial will recruit 200 older (≥60 years) patients with hypertension and MCI from 11 hospitals across China. Participants will be randomly assigned in a 1:1 ratio to the intervention group (multidomain adaptative CCT) and active control group (non-adaptive cognitive training) for 12-week cognitive training for 30 min/day and 5 days/week. Those who have completed their 12-week training in the intervention group will be rerandomised into the continuation and discontinuation training groups. All participants will be followed up to 24 weeks. Neuropsychological assessments and structural and functional 7.0 T MRI will be obtained at baseline and at 12-week and 24-week follow-up. The primary outcome is the possible improvement of global cognitive function at 12 weeks, as measured by the Basic Cognitive Aptitude Tests. Secondary and exploratory endpoints include the major cognitive domain function improvement, self-efficacy, mental health, quality of life and MRI measurements of the brain.Ethics and dissemination The trial has been approved by the institutional review board of Beijing Anzhen Hospital and thereafter by all other participating centres. Trial findings will be disseminated in peer-reviewed journals and conference presentations.Trial registration number NCT05704270.